Dermatopathology Clinicopathological Correlations - Cockerell, Clay.; Mihm Jr., Martin C.; Hall, Brian J.; Chisholm, Cary.; Jessup, Chad.; Merola, Margaret; SpringerLink (Online service) (London : Springer London : Imprint: Springer, 2014)
With significant progress as new techniques to evaluate the pathology of the skin, this book satisfies the need to provide practical clinical information and concise criteria for pathologic diagnosis for pathologists and dermatologists looking for an up-to-date resource. This superb visual reference provides detailed instruction of the experience of both diagnostic pathology and clinical dermatology. Dermatopathology: Clinicopathological Correlations is a comprehensive but concise visual reference that contains specific features on the various clinical findings and histologic findings of skin diseases. It emphasizes criteria for diagnosis to help the trainee pathologist or dermatologist decipher the most important features and make clinical decisions quickly and effectively.
Interface (Lichenoid) Dermatitides -- Spongiotic Disorders -- Psoriasiform Dermatoses -- Vesiculobullous Diseases -- Large Vessel Vasculitis -- Connective Tissue Disorders -- Panniculitides -- Metabolic disorders -- Mucinoses -- Adnexal Diseases -- Alopecias -- Granulomatous Dermatitides -- Epidermal Maturation Diseases -- Reactions to Drugs -- Bacterial Infections -- Fungal infections -- Viral infections -- Arthropod Reactions/Parasites/Other -- Pediatric inflammatory disorders -- Benign melanocytic skin lesions -- Non-melanoma skin tumors -- Cysts Epithelial tumors -- Vascular anomalies -- Fibrohistiocytic Tumors -- Soft tissue tumors (Tumors of fat and muscle) -- Neural And Neuroendocrine Tumors -- Adnexal neoplasms -- General Guide to the Diagnosis of Cutaneous Malignant Hematopoietic Proliferations -- Pediatric tumors -- Metastases.
Keywords: Medicine; Medical laboratories; Dermatology; Pathology; Medicine & Public Health; Dermatology; Pathology; Laboratory Medicine